A novel dual MoS2/FeGA quantum dots endowed injectable hydrogel for efficient photothermal and boosting chemodynamic therapy - Liu, Zeming; Zeng, Ning; Yu, Jing; Huang, Chunyu; Huang, Qinqin (Frontiers in Bioengineering and Biotechnology, 2022)
Due to its responsiveness to the tumour microenvironment (TME), chemodynamic therapy (CDT) based on the Fenton reaction to produce cytotoxic reactive oxygen species (ROS) to destroy tumor has drawn more interest. However, the Fenton’s reaction potential for therapeutic use is constrained by its modest efficacy. Here, we develop a novel injectable hydrogel system (FMH) on the basis of FeGA/MoS2 dual quantum dots (QDs), which uses near-infrared (NIR) laser in order to trigger the synergistic catalysis and photothermal effect of FeGA/MoS2 for improving the efficiency of the Fenton reaction. Mo4+ in MoS2 QDs can accelerate the conversion of Fe3+ to Fe2+, thereby promoting the efficiency of Fenton reaction, and benefiting from the synergistically enhanced CDT/PTT, FMH combined with NIR has achieved good anti-tumour effects in vitro and in vivo experiments. Furthermore, the quantum dots are easily metabolized after treatment because of their ultrasmall size, without causing any side effects. This is the first report to verify the co-catalytic effect of MoS2 and Fe3+ at the quantum dot level, as well as obtain a good PTT/CDT synergy, which have implications for future anticancer research.